Penatalaksanaan Fisioterapi Pada Kondisi Bell's Palsy Dextra Di Rsal Dr. Ramelan Surabaya - Yuliani, Nur Fitri, Dwi Kurniawati,SST.ft,M.Kes (2016)
Background: Bell's palsy is defined as a peripheral facial nerve paralysis which is caused by inflammation of myelin, the cause is unknown, in the absence of other neurologic disorders. Physiotherapy modalities that can be used to address the problems of physiotherapy in patients with Bell's palsy include Infra Red for muscle relaxation, Electrical Stimulation to facilitate muscle contraction, Massage for relaxation and maintain muscle tone and Mirror Exercise to increase muscle strength. Objective: To investigate the implementation of Physiotherapy in increasing the strength of the facial muscles and improve functional ability of facial muscles in cases of Bell's palsy using Infra Red modalities, Electrical stimulation, massage and exercise mirror. Results: After treatment for 6 times the result to an increase in muscle strength facial frontal in T1: 0 become T6: 5, muscle corrugator supercilli T1: 1 to T6: 5, muscle Proccerus T1: 1 to T6: 3, orbicularis oculi muscle T1 : 1 to T6: 5, muscle nassalis T1: 1 menjadiT6: 3, muscle depressor anguli oris T1: 0 become T6: 5, muscle zigomatikum T1: 0 become T6: 5, muscle orbicularis oris T1: 1 to T6: 5, muscle buccinator T1: 1 to T6: 5, mentalist muscle T1: 0 become T6: 5. There are functional improvement of the facial muscles on T1: 24 into 100 T6 results. Conclusion: Infra Red, Electrical Stimulation, Massage and Mirror Exercise can increase the strength of muscles of the face and improve facial muscle function in conditions of Bell's Palsy Dextra.